2014
DOI: 10.3892/ijo.2014.2559
|View full text |Cite
|
Sign up to set email alerts
|

Increased CDC20 expression is associated with development and progression of hepatocellular carcinoma

Abstract: Cell division cycle 20 (CDC20) encodes a regulatory protein interacting with the anaphase-promoting complex/cyclosome (APC/C) in the cell cycle and plays important roles in tumorigenesis and progression of multiple tumors. The present study aimed to investigate the clinical significance of CDC20 in hepatocellular carcinoma (HCC) and the role of CDC20 in the progression of HCC. By bioinformatics analysis, CDC20 was found to be the major node in HCC molecular interaction networks. Quantitative PCR and western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 32 publications
9
112
0
Order By: Relevance
“…Regarding correlation of CDC20 overexpression and tumor stage, we noted that CDC20 overexpression was significantly associated with advanced tumor stage in carcinomas of the breast, colon, endometrium, and prostate. Similar results were noted by some of the previous cohorts [25,26,39]. However, other previous studies reported that CDC20 overexpression was not correlated with tumor stage [23,24,27,[36][37][38].…”
Section: Cdc20 Immunohistochemical Expression In Malignant Tumorssupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding correlation of CDC20 overexpression and tumor stage, we noted that CDC20 overexpression was significantly associated with advanced tumor stage in carcinomas of the breast, colon, endometrium, and prostate. Similar results were noted by some of the previous cohorts [25,26,39]. However, other previous studies reported that CDC20 overexpression was not correlated with tumor stage [23,24,27,[36][37][38].…”
Section: Cdc20 Immunohistochemical Expression In Malignant Tumorssupporting
confidence: 92%
“…This difference was reaching a statistically significant level in carcinomas of the bladder, cervix, colon, endometrium, kidney, liver, ovary, prostate, and stomach. In concordance with our study, previous studies were reported such results [23,25,26,[36][37][38][39][40]. However, the difference did not reach a statistically significant level as reported by [24,27].…”
Section: Cdc20 Immunohistochemical Expression In Malignant Tumorssupporting
confidence: 80%
See 3 more Smart Citations